Nucleotide sequence of the R.meliloti nitrogenase reductase (nifH) gene. - Török, I (Nucleic Acids Res, 1981)
The nucleotide sequence of the structural gene (nifH) of nitrogenase reductase (Fe protein) from R.meliloti 41 with its flanking ends is reported. The amino acid sequence of nitrogenase reductase was deduced from the DNA sequence. The predicted R.meliloti nitrogenase reductase protein consists of 297 amino acid residues, has a molecular weight of 32,740 daltons and contains 5 cysteine residues. The codon usage in the nifH gene is presented. In the 5' flanking region, sequences resembling to consensus sequences of bacterial control regions were found. Comparison of the R.meliloti nifH nucleotide and amino acid sequences with those from different nitrogen-fixing organisms showed that the amino acid sequences are more conserved than the nucleotide sequences. This structural conservation of nitrogenase reductase may be related to its function and may explain the conservation of the nifH gene during evolution.